Morpho-Agronomic Characterization and Yield Evaluation of Doubled Haploid Eggplant (Solanum melongena L.) Lines Derived from Anther Culture - Reynatha Syafira Rizkiya; Bambang Sapta Purwoko; Awang Maharijaya; Iswari Saraswati Dewi (Universitas Sebelas Maret, 2025)
The improvement of eggplant yield through breeding is crucial. Doubled haploid technology has accelerated the development of varieties. This study utilized doubled haploid anther culture-derived lines (confirmed through flow cytometry and morphology) developed from embryos from a previous study to evaluate the morpho-agronomic performance and yield of doubled haploid eggplant lines. The experiment used a randomized complete block design (RCBD), three replications, and one factor, namely genotype (35 doubled haploid lines, three F1 varieties). Observation was made on plant height, dichotomous height, stem diameter, days to flowering and harvesting, fruit length, fruit diameter, weight per fruit, number of fruits, and fruit yield per plant. The data were analyzed using ANOVA, t-Dunnett, Tukey-Kramer at a 5% level, Pearson correlation coefficient, and selection index. The results showed significant variability in the population of doubled haploid lines. Fruit yield was positively correlated with plant height, dichotomous height, stem diameter, days to flowering, fruit length, and weight per fruit, but negatively correlated with the number of fruits per plant. These variables can be used as selection criteria because of their high heritability and genotypic coefficients of variation. The selection index revealed that the high-yielding doubled haploid lines with desirable morpho-agronomic traits were RS-P2, RS-P6, RS-P9, RS-P14, RS-P18, RS-H19, RS-H20, RS-H23, RS-H27, RS-H3, RS-M31, RS-M32, RS-M33, RS-M34, and RS-M37. The selected lines with high yield and good quality fruit, similar to the commercial hybrid parent, were Hitavi’s derived lines. All selected lines serve as the genetic basis for production improvements and long-term breeding programs for sustainable and productive eggplants that benefit farmers.